A study to prepare baby peach purée enriched whit maca, quinoa, kiwicha and cañihua - Aldana-Minaya, Horacio (2019)
This article presents the results of a research aimed at preparing a baby peach purée enriched with maca, quinoa, kiwicha and cañihua. This fruit purée is a complementary food rich in vitamins, proteins and minerals for babies from 6 months of age. At the end of the study, it is concluded that the project is technically feasible.